The implementation of the Enterprise Content Management systems in a company - Wójtowicz, Radosław (Business Informatics, 2015)
Modern technological possibilities referring to business intelligence and knowledge management support in an organization comprise mainly software which supports groupware, software used for workflow management, intranets and corporal portals, tools for remote learning, data warehouse and Enterprise Content Management systems. The latter of the mentioned information technologies currently seems to be one of the most crucial structural foundations of business intelligence and knowledge management systems which have been developing rapidly over recent years. The main objective of this paper is to present the author’s general methodology of the implementation of the ECM systems in the organization resulting from the preliminary literature review and the extensive practical experience. The first part of the study concentrates on the main definitions. The next and the most important part presents the details of the proposed methodology
Informatyka Ekonomiczna = Business Informatics, 2015, Nr 3 (37), s. 114-124
Keywords: Enterprise Content Management; IT-projects; document management; zarządzanie treścią; projekty informatyczne; zarządzanie dokumentami